The transmembrane replacement H7N9-VLP vaccine displays high levels of protection in mice - Qin, Jianru; Hu, Bing; Song, Qiqi; Wang, Ruijuan; Zhang, Xiangfei; Yu, Yaqi; Wang, Jian-Hua (Frontiers in Microbiology, 2022)
The H7N9 subtype of influenza virus has expanded rapidly in China in recent decades, generating massive economic loss and posing a significant threat to public health. In the absence of specialized antiviral treatments or long-term effective preventative vaccinations, it is critical to constantly enhance vaccines and create effective antiviral drugs to prevent the recurrence of pandemics. In this study, a transmembrane-substituted (TM) virus-like particles vaccine was created by replacing the transmembrane region of hemagglutinin (HA) protein with the transmembrane region of H3 HA protein and then used to immunize BALB/c mice. Sera and T cells were collected from the immunized mice to evaluate the passive immune effects. Our results showed that naïve mice were 80% to 100% protected against homologous and heterologous H7N9 influenza strains after receiving passive serum immunization, and the protective effect of the TM VLPs was more evident than the wild-type HA VLPs. In contrast, mice immunized with passive T cells achieved only 20% to 80% protection against homologous or heterologous strains Our findings significantly contribute to understanding the control of the H7N9 virus and development of a vaccine.